Artificial lakes delay the migration of brown trout Salmo trutta smolts: a comparison of migratory behaviour in a stream and through an artificial lake. Issue 5 (7th April 2019) - Schwinn, Michael; Baktoft, Henrik; Aarestrup, Kim; Koed, Anders
Abstract : Juvenile salmonids experience high mortality when negotiating lentic waters during their downstream migration to the sea. The development of artificial lakes and wetlands in streams has become a widely used management tool to reduce nutrient load to coastal areas. Such wetlands may threaten anadromous populations. In this study we quantify net ground speed of downstream migrating brown trout Salmo trutta smolts in equally long stream and lake sections in a Danish lowland stream and artificial lake. This was done by passive integrated transponder telemetry in 2016 and 2017. Mean net ground speed in the stream section was 36.58 and 0.8 km day −1 in the lake section. This decrease of net ground speed through the lake may lead to prolonged exposure to predators and probably contributes to high mortalities threatening anadromous populations.